“‘”: mixed-methods study exploring palliative care needs amongst refugees‘ - Priya Gupta; Ashlinder Gill; Michael Panza; Olive Wahoush; Humaira Saeed; Jehan Ara Chagani; Christiana Owoo; Christopher Klinger (Palliative Care and Social Practice)
Background: The increasing life expectancy and resultant chronic medical comorbidities have resulted in more people requiring palliative care. Unfortunately, palliative care is restricted to marginalized populations, including refugees. In Canada, refugees are only eligible for federal health insurance, which provides basic medical and social coverage until they can obtain provincial health insurance. Objectives: This study explored limitations in providing palliative care to refugees who had either federal or provincial health insurance in two care settings in Ontario, Canada. Design: An explanatory sequential mixed-methods approach guided the review of local administrative data and interview data to understand palliative care delivery for refugees. Methods: Local administrative data from a community health centre and an acute care hospital providing a palliative care approach were collected to review healthcare utilization for refugees with palliative care needs. Interviews from two focus groups with fourteen healthcare providers shared their care experiences in coordinating palliative care for refugees with either federal or provincial health insurance. Results: Refugee patients with palliative care needs appeared to be accessing acute care services frequently to meet their needs over a 5-year period. Due to a lack of citizenship or permanent residency status, many refugees have access to only federal health insurance. Compared to those with routine provincial coverage, federally insured patients were admitted more frequently. Furthermore, healthcare provider experiences revealed that refugees with only federal insurance coverage had significant barriers to accessing community palliative care support, leading to increased reliance on acute care for quality palliative care. Conclusion: This study highlights significant gaps in palliative care access for refugees, especially those with federal health insurance. Equitable access is essential in ensuring that patient-centred, quality palliative care is available to all.